(untitled) (Communications in Computational Physics, 2018)
This work develops a second-order two-scale (SOTS) model based on homogenization method to predict thermo-mechanical coupling performance of porous materials with quasi-periodic structures. For the kinds of porous materials, the corresponding material coefficients are dependent on the macroscopic variable and the radiation effect at microscale is considered in this paper. The quasi-periodic properties of the thermo-mechanical coupling models which consider mutual interaction between temperature and displacement fields are proposed at first. Then, the two-scale formulas for the thermo-mechanical coupling problems with radiation boundary conditions are derived successively, and the finite element algorithms based on the SOTS model are brought forward in detail. Finally, by some typical examples, the effectiveness and validity of the proposed algorithms are confirmed. The computational results demonstrate that the SOTS method is efficient and valid to predict the thermo-mechanical coupling properties, and can acquire the microscale information of the porous materials accurately.